PENINGKATAN HASIL BELAJAR KOGNITIF DENGAN PENGGUNAAN MODEL PROBLEM BASED LEARNING DI SD N KARANGREJO 02 SEMARANG - Fitriana Mahmudah; Choirul Huda; Henry Januar Saputra; Muh. Rofingun (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The purpose of this classroom action research is to improve the cognitive learning outcomes of fourth grade students at SD N Karangrejo 02 Semarang by applying the Problem Based Learning model. The subjects of this class action research were fourth grade students. This research was conducted for two cycles. Each cycle consists of four stages: planning, implementing, observing, and reflecting. The independent variable of this research is the Problem Based Learning model, while the dependent variable is the students' cognitive learning outcomes. Data collection techniques in this study were observation and tests. Observations were made to observe the learning process carried out by students, while tests were carried out to measure the ability of students to participate in learning. The data were analyzed quantitatively. The results showed that there was an increase in student learning outcomes in cycle I and cycle II, with a classical completeness percentage of 75% in cycle I and experiencing increased to 91.6% in cycle II. The increase in learning outcomes is caused by the application of the Problem Based Learning model which encourages students to think critically and solve problems.